Effect of Anchoring Groups on the Conduction Properties of Terphenyl Molecules Connected to Copper Leads - Setianto Setianto; Aswad H.S.; K.M. Liu (Universitas Ahmad Dahlan, 2018)
We report equilibrium and non-equilibrium conductance of terphenyl molecules with different anchoring groups including sulfur and nitrogen atom. The corresponding molecules are terphenyl-dithiols (TPDT) and diamino-terphenyl (DATP). The non-equilibrium Green's function (NEGF) technique has been implemented on the density functional tight-binding (DFTB) code to perform computations of the electronic transport properties of molecular devices. The NEGFs are used to compute the electronic density self-consistently with open boundary condition naturally encountered in transport problem which is imposed by the potentials at the contacts. As result, the value of the molecular conductance with amine groups is higher about ten times than the thiol anchored group.